2015
DOI: 10.1093/cvr/cvv255
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of IL-12p35 improves cardiac repair after myocardial infarction by promoting angiogenesis

Abstract: Deficiency of IL-12p35 limited AMI-induced cardiac injury by promoting pro-angiogenesis and anti-inflammatory functions of monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…Just as Table 4. Although IL-12 family Fairweather et al, 2003;Yang et al, 2011;Nyland et al, 2012;Jenke et al, 2014;Kong et al, 2014;Hu et al, 2014;Zha et al, 2015;Zhang et al, 2017;Miteva et al, 2017;Sesti-Costa et al, 2017;Ouyang et al, 2017;Xu et al, 2018 Zhou et al, 2001;Kempe et al, 2009;Correia et al, 2010;Lin et al, 2012;Khojasteh-Fard et al, 2012;Jin et al, 2012;Yong et al, 2013;Chistiakov et al, 2015;Abbas et al, 2015;A Shahi et al, 2015;Zykov et al, 2016;Opstad et al, 2016;Zhu et al, 2018;Rasa et al, 2018; Lee et al, 1999;Davenport and Tipping, 2003;Hauer et al, 2005;Koltsova et al, 2012;Hirase et al, 2013;Subramanian et al, 2015;Kan et al, 2016;Tao et al, 2016;Engelbertsen et al, 2018;Fatkhullina et al, 2018;Ryu et al, 2018;Huang et al, 2019;Huang et al, 2019;Wang et al, 2019;Jia et...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as Table 4. Although IL-12 family Fairweather et al, 2003;Yang et al, 2011;Nyland et al, 2012;Jenke et al, 2014;Kong et al, 2014;Hu et al, 2014;Zha et al, 2015;Zhang et al, 2017;Miteva et al, 2017;Sesti-Costa et al, 2017;Ouyang et al, 2017;Xu et al, 2018 Zhou et al, 2001;Kempe et al, 2009;Correia et al, 2010;Lin et al, 2012;Khojasteh-Fard et al, 2012;Jin et al, 2012;Yong et al, 2013;Chistiakov et al, 2015;Abbas et al, 2015;A Shahi et al, 2015;Zykov et al, 2016;Opstad et al, 2016;Zhu et al, 2018;Rasa et al, 2018; Lee et al, 1999;Davenport and Tipping, 2003;Hauer et al, 2005;Koltsova et al, 2012;Hirase et al, 2013;Subramanian et al, 2015;Kan et al, 2016;Tao et al, 2016;Engelbertsen et al, 2018;Fatkhullina et al, 2018;Ryu et al, 2018;Huang et al, 2019;Huang et al, 2019;Wang et al, 2019;Jia et...…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating animal study reports also demonstrate that treatment with exogenous recombinant murine IL-12 significantly aggravates the progression of atherosclerosis, and increases aortic atherosclerotic plaque areas in both ApoEknockout mice and in low density lipoprotein (LDL) receptordeficient mice, while cancelation the biological effects of IL-12 can significantly diminish such effects (Lee et al, 1999;Davenport and Tipping, 2003;Hauer et al, 2005). In a murine myocardial infarction model, canceling the biological effects of IL-12 alleviates cardiac dysfunction by promoting angiogenesis (Kan et al, 2016). In a recent study, Shi et al reported that knockout of IL-12p35 subunit, which can cancel the biological effects of IL-12 and IL-35, significantly aggravated Th1/Th2 and Th17/Treg imbalance and increased atherosclerotic plaque areas in ApoE mice, which may suggest that the pro-atherosclerotic effects of IL-12 can be mediated by promoting the CD4+ T lymphocyte differentiation imbalance .…”
Section: Animal Studiesmentioning
confidence: 99%
“…On the other hand, the predominance of non-inflammatory monocytes could potentially lead to a better outcome, due to the capacity of this population to enter the damaged tissues in a CX3CR1-mediated manner to repair tissue damage, secrete anti-inflammatory cytokines, and promote regeneration [ 14 , 16 ]. This positive effect has been demonstrated in myocardial infarction, where non-inflammatory patrolling monocytes enter the cardiac muscle to recover damage and promote angiogenesis [ 53 , 54 ]. Non-inflammatory monocytes also act in neurodegenerative diseases like Alzheimer’s disease, where they remove amyloid-β peptides from the brain vasculature [ 55 ], and are also known to prevent excitotoxicity [ 56 ], which could also explain the positive correlation found with survival, as glutamate-induced excitotoxicity is one of the pathological mechanisms found to participate in ALS pathogeny.…”
Section: Discussionmentioning
confidence: 99%
“…For tube formation analysis, human umbilical vein endothelial cells were seeded on Matrigel‐covered dishes as described and cultured with extracellular matrix (10% normal bovine serum albumin, and 1% penicillin/streptomycin and 1% endothelial cell growth supplement) containing concentrated fibroblast culture medium.…”
Section: Methodsmentioning
confidence: 99%